Perbandingan Plastik Dari Material-Material Bioplastik - Rosmainar, Lilis; Niholan Tukan, Dominikus; Deviyanti, Mitha (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2021)
Plastic is a polymer that has unique properties and is an extraordinary object. Polymers are materials consisting of molecules called monomers with homopolymer types. Polymers are commonly known in everyday life such as cellulose, protein, rubber, and other natural materials. The use of plastic is the impact of the development of the industrial world, technological and the increasing number of world population was increase. In Indonesian, the demand for plastic continues to increase with an average of 200 tons per year. In 2002 there were about 1,9 million tons of plastic waste, and in 2011 the amount of plastic waste increased to 2,6 million tons per year. Based on assumption of the Ministry of Environment (KLH), every day the Indonesian population can produce 0,8 kg of waste per person and if the total is 189 thousand tons of waste per day. 15% of waste produced is in the form of plastic waste or about 28,4 thousand tons per day. At first, natural polymer was used as materials for making tools and weapons. Monomers in the formation polymers are molecules that have double bonds or that have certain functional groups. Polymers are classified into natural polymers and synthetic polymers. Natural polymers such as cellulose, starch, chitin, chitosan, gelatin, dextran, alginate, pectin, guar gum and rubber are used in the manufacture of nanocomposites. Natural polymers exhibit properties such as purity, crystallinity, tensile strength, increase elasticity and have a large surface area. The conclusion is that the attractiveness of bioplastic has the same strength, but if it is added with other material, the conductivity will be stronger and better.